OUTCOME OF THE RUBBER BAND LIGATION WITH MILLIGAN MORGAN HAEMORRHOIDECTOMY - Ali, Syed Asad; Mohammad, Agha Taj; Jarwar, Mohammad; Imran, Javeria; Siddique, Akmal Jamal; Dalwani, Abdul Ghafoor (Journal of Ayub Medical College Abbottabad, 2010)
Background: Haemorrhoids is a common anorectal disease seen in our society. Conservative management is usually adopted for 1st and 2nd degree haemorrhoids. Patients who do not respond to above management are the candidates for other modalities of treatment which includes sclerotherapy, rubber band ligation, cryosurgery and stapler gun or open haemorrhoidectomy. The purpose of study was to compare the outcome of the Rubber band ligation with Milligan Morgan haemorrhoidectomy in patients with 2nd and 3rd degree haemorrhoids. Methods: Hundred diagnosed admitted patients of uncomplicated 2nd and 3rd degree piles were treated either with rubber band ligation (RBL) or open method of Milligan Morgan (OH) for the period from January 2007 to December 2007 were included in the study. Both procedures were evaluated regarding effectiveness, safety, complications after procedures, hospital stay and return to work on a written Performa. Patients with 1st and 4th degree haemorrhoids, below the age of 12 years, bleeding diathesis, associated local anorectal conditions requiring surgery, complicated haemorrhoids, recurrent and secondary haemorrhoids were excluded from the study. Follow up of all these patients was done in OPD to assess any complication and recurrence. Data was analysed through SPSS-16.0. Results: One hundred indoor patients with 2nd and 3rd degree haemorrhoids were treated either with rubber band ligation or open technique. Most (>90%) of the patients were males. Majority of the patients were in 30-33 years age group. Fresh bleeding (90%) and constipation (45%) were the commonest symptoms followed by prolapsed, discharge and irritation. Second degree was more common than 3rd degree haemorrhoids. Intensive pain was the commonest complain after both the procedures, however faecal incontinence was not reported in either group. Hospital stay was longer in open technique (70%) compare to few hours to one day in rubber band ligation group. Return to work was earlier in patients treated with rubber band ligation. Conclusion: Rubber band ligation is safe and effective method compare to open technique in 2nd and 3rd degree symptomatic haemorrhoids. Keywords: Haemorrhoids, rubber band ligation, Milligan Morgan Procedure, Outcome